Ownership of Capital in Monetary Economies and the Inflation Tax on Equity - Cosimano, Thomas; Chami, Ralph; Fullenkamp, Connel (Washington, D.C. : International Monetary Fund, 1999)
Financial instruments are subject to inflation taxes on the wealth they represent and on the nominal income flows they provide. This paper explicitly introduces financial instruments into the standard stochastic growth model with money and production and shows that the value of the firm in this case is equal to the firm's capital stock divided by inflation. The resulting asset-pricing conditions indicate that the effect of inflation on asset returns differs from the effects found in other papers by the addition of a significant wealth tax.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet